2016
DOI: 10.1016/j.bmc.2016.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of bivalent ligands targeting putative mu opioid receptor and chemokine receptor CCR5 dimerization

Abstract: Modern antiretroviral therapies have provided HIV-1 infected patients longer lifespans and better quality of life. However, several neurological complications are now being seen in these patients due to HIV-1 associated injury of neurons by infected microglia and astrocytes. In addition, these effects can be further exacerbated with opiate use and abuse. One possible mechanism for such potentiation effects of opiates is the interaction of the mu opioid receptor (MOR) with the chemokine receptor CCR5 (CCR5), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…The other explanation for better opioid efficacy might be the formation of heterodimers between chemokine receptors and opioid receptors (e.g. CCR5‐MOR, CXCR2‐DOR, CXCR4‐DOR) . To our knowledge, there is still no evidence that CCR1 creates dimers with opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other explanation for better opioid efficacy might be the formation of heterodimers between chemokine receptors and opioid receptors (e.g. CCR5‐MOR, CXCR2‐DOR, CXCR4‐DOR) . To our knowledge, there is still no evidence that CCR1 creates dimers with opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5-MOR, CXCR2-DOR, CXCR4-DOR). [99][100][101] To our knowledge, there is still no evidence that CCR1 creates dimers with opioid receptors. However, further studies are needed because it is known that CCR1 is able to heterodimerize with other chemokine receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous desensitization may explain a reduced chemotactic effect of CCR5 by pretreatment with MOR agonists [ 80 ]. Recently, synthetic, bivalent ligands composed of maraviroc and naltrexone that target the proposed CCR5-MOR heteromers/oligomers have shown that such interactions may occur in a cell type-specific manner [ 84 86 ]. The inability to form MOR-CCR5 heterodimers in CCR5-null (or MOR-null) glia may alter the cellular response to concurrent morphine exposure, contributing to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Based on previous bivalent ligand series reported from the literature, the attachment locus on naltrexone was chosen to be the C6-position after transforming the carbonyl group to the 6β-amino group. 44,45,[55][56][57][58][59] The attachment locus on IT1t was identified based on the available CXCR4-IT1t co-crystal structure (PDB: 3ODU). 30 In the binding cavity it was observed that the cyclohexyl groups adjacent to the symmetric isothiourea moiety of IT1t were pointing upward and away from the TM bundle and toward the extracellular space.…”
Section: Bivalent Ligand Rational Designmentioning
confidence: 99%